Inequalities in realised access to healthcare among recently arrived refugees depending on local access model: study protocol for a quasi-experimental study - Wenner, Judith; Rolke, Kristin; Breckenkamp, Jürgen; Sauzet, Odile; Bozorgmehr, Kayvan; Razum, Oliver (BMJ open, 2019)
INTRODUCTION: In many countries, including Germany, newly arriving refugees face specific entitlement restrictions and access barriers to healthcare. While entitlement restrictions apply to all refugees who seek protection in Germany during the first months, the barriers to access depend on the model that the states and the municipalities implement locally. Currently, two different models exist: the healthcare voucher model (HcV) and the electronic health card model (eHC). The aim of the study is to analyse the consequences of these two different access models on newly arrived refugees' realised access to healthcare. - METHODS AND ANALYSIS: The random assignment of refugees to municipalities allows for a quasi-experimental design by comparing realised access to healthcare among refugees in six municipalities in North Rhine-Westphalia which have implemented HcV or eHC. We compare realised access to healthcare using ambulatory care sensitive conditions and health expenditure as outcome indicators, and use of emergency care, preventive care, psychotherapeutic or psychiatric care, and of therapeutic devices as process indicators. Results will be adjusted for aggregated information on age, sex, socioeconomic structure of the municipalities and density of general practitioners or specialists. - ETHICS AND DISSEMINATION: We cooperated with local welfare offices and the statutory health insurance for data collection. Thereby, we were able to avoid recruiting large numbers of refugee patients immediately after arrival while their access and entitlement to healthcare are restricted. We developed an extensive data protection concept and ensured that all data collected are fully anonymised. Results will be published in peer-reviewed journals and summarised in reports to the funding agency.